If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -5g + -1f + -2g = 0 Reorder the terms: 3f + -1f + -5g + -2g = 0 Combine like terms: 3f + -1f = 2f 2f + -5g + -2g = 0 Combine like terms: -5g + -2g = -7g 2f + -7g = 0 Solving 2f + -7g = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '7g' to each side of the equation. 2f + -7g + 7g = 0 + 7g Combine like terms: -7g + 7g = 0 2f + 0 = 0 + 7g 2f = 0 + 7g Remove the zero: 2f = 7g Divide each side by '2'. f = 3.5g Simplifying f = 3.5g
| 20/2.24=x | | 2x+12=5-15x | | 2r/3=10-r | | 4x-28=4x-7 | | 66x+74=y | | v=2.25(2)+4 | | 6/21=8/x | | (7+4)+(3x+9)=180 | | 8/(m+10)=4/(2m-7) | | 15a-20b= | | -2x+2y=0 | | x+26-(-38*3)=728 | | 3(x+3)=3(x+8) | | 2x+0=2x | | 12-5a=2a-9 | | (n-8)=-2 | | (10v^4-2v^2+6v^3-7)-(9-v+2v^4)=0 | | 6.8x+3=5.8x | | 5x-18=3x | | -2a+5a= | | 2(8-4y)-5y=29 | | -2(6-10x)=10(2x-6)+(x+8) | | (8/y+3)-(2/y-3)=(12/y^2-9) | | 8/(2x+3)=4/(x-1) | | 2x^2=10-x | | 0.12x=0.60 | | X(2x+1)=21 | | -x+2x+y=y | | (7q-3q^3)+(16-8q^3+5q^2-q)=0 | | 2x^2=600 | | (x+1)/3=(2x+2)/6 | | 2x=-2x+4 |